Шайдың әр түрлі сорттарындағы Р витамині мөлшерін сандық анықтау - Кинжекеева, Г.М. (My University, 2013)
The paper demonstrates the physiological importance, sources of vitamin P and the results determine the quantity of the product in various varieties of tea by chemical analysis.